Humanitarian logistics: A multicriteria decision approach for venezuelan refugee resettlement process - Carvalho, Natália Macedo; de Oliveira Gomes, Pedro Fernandes; Briesemeister, Roberta; Chiroli, Daiane Maria de Genaro (Decision Making and Analysis, 2024)
The number of people seeking shelter in other countries is increasing due to the escalating humanitarian and political crisis. In South America, the case of Venezuelan refugees is known worldwide as the cause of local political crisis. Due to its geographic proximity to Brazil, Venezuelans tend to migrate in their primary movement to Brazilian cities that are close to the border between the two countries. Afterwards, their secondary movement is characterized by their spread throughout the Brazilian territory, also known as resettlement. In this sense, this paper aims to propose a multicriteria decision making approach for choosing the best cities as resettlement locations for the Venezuelan refugees in Brazil. The study was conducted considering fifteen cities in the state of Amazonas. The multicriteria decision making methods Best-Worst Method (BWM) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) were applied. The BWM method focused on determining the weights of the decision criteria, while the TOPSIS method was instantiated to rank the decision alternatives. The decision criteria that are associated with employment and basic sanitation were given the highest weights, as they represent the most important needs of the refugees. The analysis of the decision alternatives showed that the city of Manaus, Humaitá and Iranduba were the top three in the alternatives ranking. Although these alternatives have different characteristics reflected in their performance regarding the decision criteria, they are recommended as resettlement locations because they can satisfy the most important needs of the refugees.